Research progress of rehabilitation nursing for stroke patients (脑卒中康复护理研究进展) - WANG Li (王丽) (Association of Integrative Nursing, 2024)
Hemiplegia, aphasia and cognitive impairment are common consequences of stroke and have direct implications for post-stroke functioning and quality of life. Therefore, it is imperative to reduce the disability rate following stroke by early rehabilitation intervention. This paper reviewed studies on stroke rehabilitation nursing in perspectives of rehabilitation opportunity, psychological care, body position management, motor function rehabilitation exercise, dysphagia nursing and activity of daily living, and provided reference for improving prognosis and quality of life after stroke. (脑卒中后可能遗留偏瘫、失语、认知障碍等后遗症, 严重影响患者日常生活。早期进行康复干预对降低脑卒中致残率有着重要的临床意义。本研究就脑卒中患者的早期康复时机、心理康复护理、体位摆放、运动功能康复训练、吞咽障碍的护理、日常生活训练等应用现状进行综述, 旨在为改善脑卒中患者预后提供参考。)